Pulse Clarithromycin Therapy In Severe ACNE Vulgaris - Rathi Sanjay K (Wolters Kluwer Medknow Publications, 2002)
Three patients with severe acne vulgaris, not responding with long courses of doxycycline, minocycline and erythromycin were given oral clarithromycin in pulsed regimen. The patients were given 7 days course of clarithromycin 250mg twice daily, which was repeated after a gap of 10 days. Such 3 courses were given. The lesions responded significantly. No significant side effect was noted. Pulse clarithromycin therapy seems to be a good alternative and effective tool in the management of severe acne vulgaris.